2012
DOI: 10.1103/physreva.86.042510
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic atomic data for Cu-like tungsten

Abstract: Energy levels, radiative transition probabilities, and autoionization rates for [Ne]3s 2 3p 6 3d 9 4l nl, [Ne]3s 2 3p 5 3d 10 4l nl (n = 4-6), and [Ne]3s 2 3p 6 3d 9 5l nl (n = 5-7) states in Cu-like tungsten (W 45+ ) are calculated using the relativistic many-body perturbation theory method (RMBPT code), the multiconfiguration relativistic Hebrew University Lawrence Livermore Atomic Code (HULLAC), and the Hartree-Fock relativistic method (COWAN code). Autoionizing levels above the [Ne]3s 2 3p 6 3d 10 threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 48 publications
8
35
0
2
Order By: Relevance
“…The same is also true for the corresponding transition dipole matrix elements presented in Table II. They show excellent agreement with the matrix elements obtained by the precision linearized coupled-cluster method [38].…”
Section: A Electronic Structure Of LI Atomsupporting
confidence: 71%
“…The same is also true for the corresponding transition dipole matrix elements presented in Table II. They show excellent agreement with the matrix elements obtained by the precision linearized coupled-cluster method [38].…”
Section: A Electronic Structure Of LI Atomsupporting
confidence: 71%
“…For atomic theory, highly charged tungsten ions are important because of quantum electrodynamics and relativity effects on atomic structure. A lot of research work has been performed on tungsten ions [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Recently, measurements were reported by Beiersdorfer et al [39] of L-shell X-ray emission spectra for Ne-like W 64+ ions.…”
Section: Introductionmentioning
confidence: 95%
“…Further, Sansonetti et al [44] provided the transition data with energy levels for Ba XXVIII and other barium ions. Safronova et al [45] presented the energy levels, transition wavelengths along with weighted oscillator strengths and transition probabilities for W 45+ by applying Cowan code and RMBPT. Suzuki et al [46] have observed EUV spectra for highly ionized Gd and Nd ions including Cu-like Gd and Nd by solid pellet injection in Large Helical device (LHD) plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Wavelengths (Å) of SXR Nα strong transitions 4-13, 5-14, 6-15 and 7-16 for Cu-like ions: predicted wavelength (λ p ) and theoretical and experimental wavelength (λ c ), atomic number (Z).References: a-[26],e-[54], f-[10], l-[44], m-[43], n-[40], o-[24], q-[42], r-[45], s-[25] , t-[57], u-[27], v-[58], w-[59], y-[60].Table 9. Moseley's parameters K and σ for Nα strong transitions of Cu-like ions.…”
mentioning
confidence: 99%